Measurements of plutonium, 237Np, and 137Cs in the BCR 482 lichen reference material - Lavelle, Kevin B.; Miller, Jeffrey L.; Hanson, Susan K.; Connick, William B.; Spitz, Henry B.; Glover, Samuel E.; Oldham, Warren J. (Journal of radioanalytical and nuclear chemistry, 2016)
Select anthropogenic radionuclides were measured in lichen reference material, BCR 482. This material was originally collected in Axalp, Switzerland in 1991 and is composed of the epiphytic lichen Pseudevernia furfuracea . Samples from three separate bottles of BCR 482 were analyzed for uranium, neptunium, and plutonium isotopes by inductively coupled plasma mass spectrometry and analyzed for 137 Cs by gamma-ray spectrometry. The isotopic composition of the radionuclides measured in BCR 482 suggests contributions from both global fallout resulting from historical nuclear weapons testing and more volatile materials released following the Chernobyl accident.